Homogenized molecular chain plasticity simulation for crystalline polymer using craze evolution model based on chemical kinetics. (October 2015) - Hara, H.; Shizawa, K.
Abstract: Most of the polymers used as structural materials are crystalline polymers that are mixtures composed of glassy and crystalline phases. The fracture of ductile polymers occurs on the boundary between the regions with oriented and non-oriented molecular chains after neck propagation. This behavior is caused by the concentration of craze, which is a type of microscopic damage typically observed in polymers. In this paper, by introducing the strain rate and strain dependence of crazing into the activation energy, a craze evolution equation that describes the nucleation and growth of craze is newly proposed on the basis of chemical kinetics. Then, using a multiscale material model that homogenizes the mixed structure of the glassy phase expressed by the molecular chain plasticity model and the crystalline phase represented by the conventional crystal plasticity model in unit cell, a finite element (FE) simulation coupled with the craze evolution equation is carried out for a crystalline polymer subjected to a uniaxial load. We attempt to reproduce the formation and propagation of the high-strain-rate shear band and the craze-concentration region that occur with neck propagation and to directly visualize the orientation of molecular chains inside the macroscopic structure. The relationship between the deformation behaviors of a macroscopic plate and the unit cell is investigated. In addition, the nonlinear strain recovery in the unloading process observed in a stress–strain curve is also represented through the use of an inelastic response law based on the change in the local free volume as a material response law for glassy polymer. Applying a criterion for a fracture prediction obtained from the fibril strength to the numerical results, fracture prediction based on the craze concentration is demonstrated. Highlights: Crystal-plasticity based models are employed for glassy and crystalline phases. Craze evolution equation is newly proposed according to chemical kinetics. A multiscale FE analysis is carried out for PP using homogenization method. Propagation of craze-concentration region with strain-rate shear band is reproduced. Nonlinear strain recovery due to viscoelasticity is represented in unloading process.